Sustainable engineered geopolymer composites incorporating recycled waste rubber as full replacement of fine aggregates - Feihong Wan; Yutao Guo; Miaozi Zheng; Binbin Li; Ahmed Y. Elghazouli (Journal of Materials Research and Technology, 2025)
Recycled waste rubber from end-of-life tyres offers a sustainable alternative to natural aggregates in construction materials. Most existing studies have however typically limited the rubber replacement ratios to below 30 % (by volume) due to the associated strength reduction. This study addresses this limitation by developing rubberised engineered geopolymer composites (RU-EGCs) in which fine silica sand (FSS) is replaced by high volume of rubber (0 %, 30 %, 60 %, and 100 %), aiming to simultaneously improve ductility and sustainability. A detailed experimental evaluation is conducted in this study through mechanical testing, microstructural characterisation, and life cycle assessment (LCA), for understanding the fundamental performance of RU-EGCs. The results show that increasing the rubber replacement ratio reduces the compressive strength yet markedly improves the ductility and crack control. The fully rubberised mixture is shown to achieve a tensile strain of 7.7 % and maintains a compressive strength of 47 MPa. X-ray computed tomography (X-CT) and backscattered electron (BSE) imaging analyses also reveal increased porosity and a wider interfacial transition zone (ITZ) with rubber incorporation, which facilitate early crack initiation. Nevertheless, strong fibre/matrix bonding ensures sufficient bridging stress and energy dissipation, hence promoting a transition toward high ductility. Moreover, the LCA results demonstrate notable environmental benefits whereby, compared to typical engineered cementitious composites (ECC), the developed RU-EGCs achieves more than 40 % reduction in both embodied carbon and material cost. Overall, the findings of this investigation lays down an approach for designing sustainable ultra-high-ductility EGC through high-volume rubber utilisation, offering strong potential for practical application.